2022
DOI: 10.3389/fmed.2022.937216
|View full text |Cite
|
Sign up to set email alerts
|

A model for predicting fall risks of hospitalized elderly in Taiwan-A machine learning approach based on both electronic health records and comprehensive geriatric assessment

Abstract: BackgroundsFalls are currently one of the important safety issues of elderly inpatients. Falls can lead to their injury, reduced mobility and comorbidity. In hospitals, it may cause medical disputes and staff guilty feelings and anxiety. We aimed to predict fall risks among hospitalized elderly patients using an approach of artificial intelligence.Materials and methodsOur working hypothesis was that if hospitalized elderly patients have multiple risk factors, their incidence of falls is higher. Artificial inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
5
1
Order By: Relevance
“…However, the FP test only evaluates the physical aspects of frailty, while frailty is acknowledged to be a multifaceted state that includes not only physical dimensions, but also social, cognitive, and psychological dimensions (5,6). Gaitrelated mobility is a key physical ability that has been linked to frailty and is often used as a predictor of future health outcomes (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…However, the FP test only evaluates the physical aspects of frailty, while frailty is acknowledged to be a multifaceted state that includes not only physical dimensions, but also social, cognitive, and psychological dimensions (5,6). Gaitrelated mobility is a key physical ability that has been linked to frailty and is often used as a predictor of future health outcomes (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…CGA has also been used in machine learning to better evaluate older patients with atrial fibrillation (30). Our previous work has also showed that CGA combined with EHR can predict fall risk among the older adults (16). Future studies are still warranted for both identification and intervention in the promotion of physical function during hospitalization after any machine learning prediction.…”
Section: Discussionmentioning
confidence: 92%
“…With advancing technology and improved medical informatics, some researchers have predicted adverse outcomes in hospitalized patients based upon electronic health records (EHRs), however data pulled from EHRs also have some limitations (13,14). Therefore, many scientists now use a machine learning model to predict adverse outcomes in older adults (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the other four machine learning models, the XGBoost model has the following advantages: it has no explicit linearity requirement for the data distribution and automatically detects non-linear relationships and interaction effects using the relevant factors; it can make full use of missing data without filling in the data and can more realistically reflect the original results expressed by the data; the XGBoost model has the advantage of handling large samples of data (33), learning and remembering as it analyses and processes the data and improving its predictive power; the model trained with a large amount of data is more reliable than a machine learning model fitted to a small sample of individual tests (34). The XGBoost model has the advantage of being able to learn and remember as the data is analyzed and processed, and to improve its predictive power (35); a model trained on a large amount of data is more reliable than a machine learning model fitted to a small sample of individual tests, and has a high clinical application in predicting classification outcomes (36).…”
Section: Discussionmentioning
confidence: 99%